2019
DOI: 10.1101/547943
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Convergent seed color adaptation during repeated domestication of an ancient new world grain

Abstract: Out of the almost 2,000 plants that have been selected as crops, only a few are fully domesticated, and many intermediates between wild plants and domesticates exist. Genetic constraints might be the reason why incompletely domesticated plants have few characteristic crop traits, and retained numerous wild plant features. Here, we investigate the incomplete domestication of an ancient grain from the Americas, amaranth. We sequenced 121 genomes of the crop and its wild ancestors to show that grain amaranth has … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…1 B and C ). Genetic differentiation (F ST ) between individuals with ancestry homogenous for different lineages at K = 2 was 0.212, on par with or greater than that between other congeners (30). Moreover, both longitude and latitude significantly explained both PC1 and PC2 of the SNP matrix ( SI Appendix , Table S2), with PC1 separating var.…”
Section: Demography Of Amaranthus Tuberculatusmentioning
confidence: 88%
“…1 B and C ). Genetic differentiation (F ST ) between individuals with ancestry homogenous for different lineages at K = 2 was 0.212, on par with or greater than that between other congeners (30). Moreover, both longitude and latitude significantly explained both PC1 and PC2 of the SNP matrix ( SI Appendix , Table S2), with PC1 separating var.…”
Section: Demography Of Amaranthus Tuberculatusmentioning
confidence: 88%
“…1B,C). Genetic differentiation (F ST ) between individuals with ancestry homogenous for different lineages at K=2 was 0.212, on par with or greater than that between congeners (29). Moreover, both longitude and latitude significantly explained both PC1 and PC2 of the SNP matrix (Sup Table 2), with PC1 separating var.…”
Section: Demography Of Amaranthus Tuberculatusmentioning
confidence: 95%
“…Adebo et al [160] reported two colours for seed coat (black and brown) among Corchorus olitorius cultivars from Benin. In amaranth species, a MYB-like transcription factor gene controls the seed colour variation especially between the ancestor, which is black, and the domesticated species, which is white [161]. Most of the seed dormancy constraints observed in TLVs seeds are due to the seed coat structure.…”
Section: Seed Coat Componentsmentioning
confidence: 99%